Penerapan Pembelajaran Model Jigsaw Untuk Meningkatkan Minat Dan Hasil Belajar Fisika - Muhammad Luqman Hakim Abbas (Department of Physics Education, Universitas Mataram, 2019)
This research is a classroom action research which aims to improve learning outcomes physics class in Madrasah Aliyah Al-Ihsan Kalijaring. The sample used in this research is class XI MIPA totaling 31 people, by applying science technology society learning model.ÃÂ This study is successful if students achieve learning outcomes classical completeness 85% with the value of each student reach Ã¢â°Â¥ 75. Based on the evaluation of the obtained value of the average grade in the first cycle of 77.01 with 74.42% classical completeness. In the second cycle learning outcomes of students has increased, with an average grade of 93.02 and classical completeness amounted to 90.46%. Based on the interest questionnaire that has been distributed to students before and after the action, data is obtained that the student's interest has increased. The indicators that showed an increase were the total score obtained before the administration of action was 1842 with an average of 42.84 increasing to 2326 with an average of 54.86. Based on the results of the study it can be concluded that by applying the Jigsaw cooperative learning model can increase interest and learning outcomes in physics class XI MIPA Madrasah Aliyah Al-Ihsan Kalijaring Tembelang Jombang.ÃÂ